Sulfate activation in mitosomes plays an important role in the proliferation of Entamoeba histolytica. - Fumika Mi-ichi; Takashi Makiuchi; Atsushi Furukawa; Dan Sato; Tomoyoshi Nozaki (Public Library of Science (PLoS), 2011)
Mitochondrion-related organelles, mitosomes and hydrogenosomes, are found in a phylogenetically broad range of organisms. Their components and functions are highly diverse. We have previously shown that mitosomes of the anaerobic/microaerophilic intestinal protozoan parasite Entamoeba histolytica have uniquely evolved and compartmentalized a sulfate activation pathway. Although this confined metabolic pathway is the major function in E. histolytica mitosomes, their physiological role remains unknown. In this study, we examined the phenotypes of the parasites in which genes involved in the mitosome functions were suppressed by gene silencing, and showed that sulfate activation in mitosomes is important for sulfolipid synthesis and cell proliferation. We also demonstrated that both Cpn60 and unusual mitochondrial ADP/ATP transporter (mitochondria carrier family, MCF) are important for the mitosome functions. Immunoelectron microscopy demonstrated that the enzymes involved in sulfate activation, Cpn60, and mitochondrial carrier family were differentially distributed within the electron dense, double membrane-bounded organelles. The importance and topology of the components in E. histolytica mitosomes reinforce the notion that they are not "rudimentary" or "residual" mitochondria, but represent a uniquely evolved crucial organelle in E. histolytica.